The Effect of Good Corporate Governance on Sustainability Reporting: Evidence from Bank and Non-Bank - Reza Amanda Bahtiari; Agus Kurniawan; Gustika Nurmalia (Department of Islamic Banking, 2025)
Purpose – The objective of this inquiry is to determine the impact of corporate governance on the level of sustainability report disclosure, with industry type as a control variable. Methodology – This study employs quantitative research methodologies. The company’s official website serves as a primary source of data for financial statements and sustainability reports, which are integral to the data collection process. Regression analysis of panel data utilizing Eviews 13 constitutes one of the employed data analysis techniques. Purposive sampling is the sampling method employed for the data collection process. After a five-year monitoring period, the sample comprised 14 companies that demonstrated exemplary corporate governance practices during the 2019-2023 timeframe. Findings – The investigation revealed that the board of directors and independent commissioners exerted no influence on the level of disclosure in the sustainability report. Conversely, the audit committee had a negative impact, while industry-specific control variables exhibited a positive impact. Consequently, based on the findings of the investigation, all three components of effective corporate governance—independent commissioners, directors, and audit committees—exert influence on the level of disclosure in sustainability reports. Implications – The outcomes of the inquiry provide investors with a comprehensive understanding of a company’s sustainability, enabling them to make informed investment decisions. These insights highlight the crucial role of high-quality sustainability report disclosures in fostering effective corporate governance and ensuring long-term sustainability. Originality – This inquiry stands out as it analyzes the impact of the pandemic from 2019 to 2023, utilizing CGPI-rated businesses as the primary subjects and incorporating industry types as control variables.